2012
DOI: 10.1080/ac.67.5.2174140
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular repair of the left subclavian artery after gunshot wound: an alternative to surgical treatment

Abstract: Penetrating injuries of the subclavian artery are associated with a high morbidity and mortality rate. Endovascular treatment with covered stents (stent grafts) has emerged as an eff ective alternative to surgery, but this new technique is not exempt from complications. We report the case of a male gunshot victim, treated by a covered stent for haemorrhagic shock due to partial subclavian rupture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…Traumatic injuries of the subclavian arteries are uncommon, but are associated with elevated morbidity and mortality rates. [2][3][4] Penetrating traumas are the most common causes. 3 Incidence ranges from 2.3% to 3.9%.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Traumatic injuries of the subclavian arteries are uncommon, but are associated with elevated morbidity and mortality rates. [2][3][4] Penetrating traumas are the most common causes. 3 Incidence ranges from 2.3% to 3.9%.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4] Penetrating traumas are the most common causes. 3 Incidence ranges from 2.3% to 3.9%. [4][5][6] In a review of 262 cases of traumatic fistulas, Rich et al 6 found one case of fistula of subclavian vessels.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations